Orphan Care : (Kumarian Press, 2012)
In Orphan Care, Jo Bailey and her contributors argue that efforts to help orphans have been marred by over-reliance on models and practices originating in the developed countries of the Global North. Each chapter covers the country s history and background of policy and services to orphans, the dominant reasons children are brought into care; and the prevailing forms of current orphan services.